Sciencepreneurship : science, entrepreneurship and sustainable economic growth - Formica, Piero (Emerald points., 2023)
Sciencepreneurship explores the symbiotic relationship between science, entrepreneurship and sustainable economic growth. It argues that like artists, writers and educators, scientists and entrepreneurs foster social progress and provide opportunities to advance sustainable and environmentally friendly economic development.